2017
DOI: 10.1371/journal.pone.0176189
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity and structure-activity relationship of cinnamic acid esters and their derivatives as potential antifungal agents for plant protection

Abstract: A series of cinnamic acid esters and their derivatives were synthesized and evaluated for antifungal activities in vitro against four plant pathogenic fungi by using the mycelium growth rate method. Structure−activity relationship was derived also. Almost all of the compounds showed some inhibition activity on each of the fungi at 0.5 mM. Eight compounds showed the higher average activity with average EC50 values of 17.4–28.6 μg/mL for the fungi than kresoxim-methyl, a commercial fungicide standard, and ten co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 42 publications
(45 reference statements)
2
24
0
Order By: Relevance
“…Moreover, previous studies have shown the role of HCA derivatives as antifungal agents that can be used for plant protection. 14) Since HCA is present in cereals and many other plants, it is beneficial for human consumption in addition to being toxic to pathogens. Recent investigations have revealed that cinnamic acid derivatives such as ferulic acid (3-methoxy-4-hydroxycinnamic acid) and isoferulic acid (3-hydroxy-4-methoxycinnamic acid) are the most bioactive components present in the rhizomes of Cimicifuga heracleifolia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies have shown the role of HCA derivatives as antifungal agents that can be used for plant protection. 14) Since HCA is present in cereals and many other plants, it is beneficial for human consumption in addition to being toxic to pathogens. Recent investigations have revealed that cinnamic acid derivatives such as ferulic acid (3-methoxy-4-hydroxycinnamic acid) and isoferulic acid (3-hydroxy-4-methoxycinnamic acid) are the most bioactive components present in the rhizomes of Cimicifuga heracleifolia.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to electron-donating groups, our results from cinnamic acid analogs were not well aligned with that of “ethyl” cinnamic acid derivatives [ 39 ]. For example, in our study, 4-methoxycinnamic acid ( p -substitution) belongs to the Group 1, possessing the highest antifungal activity ( Table 1 ), while 2- and 3-methoxycinnamic acids ( o - and m -substitution, respectively) belong to Group 3, showing no antifungal activity ( Table 1 ).…”
Section: Resultsmentioning
confidence: 75%
“…Antifungal activities of various cinnamic acid derivatives have been documented elsewhere [ 37 , 38 , 39 ]. Structure-activity relationship revealed that the substitution design of cinnamic phenyl ring significantly affected antifungal activity [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously described, esters and amides of coumaric, ferulic and caffeic acid possess numerous biological activities, e.g., antioxidant [ 82 , 83 , 86 , 89 , 94 , 95 , 96 ], anticancer [ 78 , 87 , 92 ], antibacterial [ 82 , 97 , 98 , 99 ], antifungal [ 100 , 101 , 102 ], antiviral [ 82 , 90 , 103 ], anti-inflammatory [ 104 , 105 , 106 ], and many other activities [ 84 , 107 , 108 ]. The most commonly described health beneficial properties of HCAs and their derivatives is antioxidant activity due to the phenolic hydroxyl group(s) on the main aromatic ring, which possess(es) the ability to react with free radicals and reactive oxygen species forming a resonance-stabilized phenoxyl radical.…”
Section: Synthesis and Properties Of Natural And Synthetic Hydroxymentioning
confidence: 99%